"The phenomenon of climate change, its nature, causes, and the resulting impacts - Emad Sahib Al- Mutar , Researcher. Hassan; Jabbar Creedy Al-Qadi , Prof. Dr. Ali (Basra studies journal, 2023)
The phenomenon of climate change is currently one of the most important environmental issues, resulting from natural factors such as gases emitted from volcanoes or greenhouse gases produced by glasshouses, as well as human factors arising from increased human activities and the consumption of non-renewable energy sources. This poses a threat to global security. Therefore, climate change has become an undeniable matter, comparable in danger to human wars. Thus, climate change is now considered a threat to peace and international security. The Canadian climate scientist and 2019 Champions of the Earth award winner, Catherine Hayhoe, described this issue by stating, "We humans all want the same thing – a safe place to live on this planet we call home – and while our work must remain objective and unbiased, we increasingly find our voices rising to add to the clear message: that climate change is real, humans are responsible, impacts are serious, and we must act now." Due to the seriousness of the consequences of climate change, it has become imperative for the international community to establish regulations and foundations for managing this complex issue. Efforts should be made to address it before it worsens, with the primary global goal being to reduce the Earth’s temperature by 2 to 1.5 degrees Celsius and restore it to pre-industrial levels by the year 2050.